Partial purification of Amylase from isolate 1B using Ammonium Sulfate - Abd Rahman, Abd Faiziladha Syahmi (2018)
Ammonium sulfate precipitation method is a method of precipitating the protein in the presence of excess salt which is the ammonium sulfate. The objective of this research is to partially purify amylase by using ammonium sulfate precipitation method. This research was conducted by using a stock culture strain obtained from Microbial Technology Laboratory, Universiti Malaysia Kelantan. The strain has been originally isolated from soil. The strain was cultured on 10% starch agar with 24 hours duration at 37 °C and was then flooded with Gram's iodine solution for starch hydrolysis test and the formation of clearance zone around the microbe. Double screening of starch hydrolysis test was also conducted for Relative Amylolytic Activity (RAA). A single colony of the best strain (1B) was then inoculated into nutrient broth with 24 hours duration at 37 °C under 150 rpm stirring condition. Then, amylase activity was assayed and the protein content was obtained by using A280 absorbance. In this research, the sample with 80% ammonium sulfate concentration contains the best partial purified enzyme with 72% yield and 0.9 protein fold.